Fluoxetine potentiation of Omega-3 fatty acid antidepressant effect: evaluating pharmacokinetic and brain fatty acid-related aspects in rodents - Laino, Carlos Horacio; Garcia, Pilar Teresa; Podestá, María Fernanda; Höcht, Christian; Slobodianik, Nora Haydee; Reines, Analia Gabriela (2018)
We previously reported that combined fluoxetine administration at antidepressant doses renders additive antidepressant effects, whereas non-antidepressant doses potentiate the omega-3 fatty acid antidepressant effect. In the present study, we aimed to evaluate putative pharmacokinetic and brain omega-3 fatty acid-related aspects for fluoxetine potentiation of omega-3 fatty acid antidepressant effect in rats. Coadministration of omega-3 fatty acids with a non-antidepressant dose of fluoxetine (1 mg/kg day) failed to affect both brain fluoxetine concentration and norfluoxetine plasma concentration profile. Fluoxetine plasma concentrations remained below the sensitivity limit of the detection method. Either antidepressant (10 mg/kg day) or non-antidepressant (1 mg/kg day) doses of fluoxetine in combination with omega-3 fatty acids increased hippocampal docosapentaenoic acid (DPA, 22:5 omega-3) levels. Although individual treatments had no effects on DPA concentration, DPA increase was higher when omega-3 were combined with the non-antidepressant dose of fluoxetine. Chronic DPA administration exerted antidepressant-like effects in the forced swimming test while increasing hippocampal docosahexaenoic (22:6 omega-3) and DPA levels. Our results suggest no pharmacokinetic interaction and reveal specific hippocampal DPA changes after fluoxetine and omega-3 combined treatments in our experimental conditions. The DPA role in the synergistic effect of fluoxetine and omega-3 combined treatments will be for sure the focus of future studies.